VD_FINDINFO HC / 2013 / 709 vom 4. November 2013 - VD Tribunal cantonal (2013)
PROTECTION DE L'UNION CONJUGALE, AUTONOMIE, OBLIGATION D'ENTRETIEN, CONJOINT | 163 CC, 176 al. 1 ch. 1 CC, 176 al. 1 ch. 3 CC, 2 CC